Effect of Folic Acid Supplementation in Pregnancy on Preeclampsia: The Folic Acid Clinical Trial Study - Shi Wu Wen; Josee Champagne; Ruth Rennicks White; Doug Coyle; William Fraser; Graeme Smith; Dean Fergusson; Mark C. Walker (Journal of Pregnancy)
Preeclampsia (PE) is hypertension with proteinuria that develops during pregnancy and affects at least 5% of pregnancies. The Effect of Folic Acid Supplementation in Pregnancy on Preeclampsia: the Folic Acid Clinical Trial (FACT) aims to recruit 3,656 high risk women to evaluate a new prevention strategy for PE: supplementation of folic acid throughout pregnancy. Pregnant women with increased risk of developing PE presenting to a trial participating center between 80/7 and 166/7 weeks of gestation are randomized in a 1 : 1 ratio to folic acid 4.0 mg or placebo after written consent is obtained. Intent-to-treat population will be analyzed. The FACT study was funded by the Canadian Institutes of Health Research in 2009, and regulatory approval from Health Canada was obtained in 2010. A web-based randomization system and electronic data collection system provide the platform for participating centers to randomize their eligible participants and enter data in real time. To date we have twenty participating Canadian centers, of which eighteen are actively recruiting, and seven participating Australian centers, of which two are actively recruiting. Recruitment in Argentina, UK, Netherlands, Brazil, West Indies, and United States is expected to begin by the second or third quarter of 2013. This trial is registered with NCT01355159.